Priorities, challenges and opportunities for supplying tree genetic resources - Kettle, Christopher J.; Atkinson, Rachel; Boshier, David; Ducci, Fulvio; Dawson, Ian K.; Ekué, Marius; Elias, Marlène; Graudal, Lars; Jalonen, Riina; Koskela, Jaarko; Monteverdi, Maria Cristina; Thomas, Evert; et al. (2020)
Special issue on Landscape restoration